PENINGKATAN KAPASITAS TENANT DI POSKO JASUDA DENGAN MENERAPKAN TEKNOLOGI INFORMASI DAN BUSSINESS MODEL CANVAS - Indrabayu, Indrabayu; Munir, Abdul Razak; Areni, Intan Sari (Panrita Abdi - Jurnal Pengabdian pada Masyarakat, 2019)
Abstract. POSKO (Center Operation of Communication Community System) Jasuda is a place for micro business communities in tamalanrea sub-district which is partner in the services that have been done during KKN Unhas 99. Analysis result of the situation and condition shows that there are 3 things that need special treatment in POSKO Jasuda to develop business unit opportunity. These three things need to reintroduce BMC, hybrid digital assistance and improvement of existing information system. This service aims to reform management information system of the posko unit that can be used to assist small and medium enterprises (SMEs) that built. Reintroduce BMC to SMEs that built which is the fundamental business feasibility analysis and provide mentoring for business improvement and IT skill for staff in the posko unit so that comunity can develop and raise SMEs that built. In addition, the existing SIM in the posko will be upgraded to fulfill the needs of SMEs and to develop marketing system of social media for each tenant. This service activity is integrated with Hasanuddin University KKN program, especially general debriefing (preparation of the training modul, recruitment/registration and training/student training. Internal debriefing is done separately by each thematic scheme of KKN, adjusting provision for KKN participants’ before joining partner. Joint activities between students and SMEs community in POSKO JASUDA, start from BMC model introduction training, SMEs shaping process that is in line with the SIM advancing program and coaching training and 1 month of mentoring. KKN participants are divided in to 10 groups to assist tenants and 1 group for POSKO JASUDA. Result of this KKN-PPM service shows tremendous impact on the capacity and sustainability of tenants who are all micro-scale businesses. Keywords: ICT technology, BMC, KKN-PPM Dikti Abstrak. POSKO (Pusat Operasi Sistem Komunitas Komunikasi) Jasuda adalah suatu wadah komunitas Usaha Mikro di kecamatan Tamalanrea yang menjadi mitra tempat kegiatan pengabdian yang dilakukan pada KKN Unhas gel. 99. Hasil analisis situasi dan kondisi menunjukkan terdapat tiga hal yang perlu penanganan khusus di POSKO Jasuda untuk keberlangsungan ataupun peluang berkembangnya unit usaha di dalamnya. Ketiga hal tersebut adalah perlunya reintroduced BMC (Business Model Canvas), pendampingan digital hybrid dan perbaikan sistem informasi eksisting. Tujuan pengabdian yang dilakukan adalah reformasi ulang dari Sistem Informasi Manajemen unit POSKO agar dapat berfungsi efisien untuk UKM binaan; Melakukan reintroduced BMC ke para UKM binaan yang merupakan fundamental analisis kelayakan usaha; dan Memberi mentoring perbaikan usaha dan IT skill bagi para staf di unit POSKO sehingga komunitas dapat mengembangkan dan membesarkan para unit UKM binaan. Selain itu SIM eksisiting di POSKO akan di upgrade untuk memenuhi kebutuhan UKM dan mengembangkan sistem marketing social media bagi setiap tenant. Kegiatan pengabdian ini diintegrasikan dengan program KKN Universitas Hasanuddin khususnya pembekalan umum (Persiapan Modul Latih, Perekrutan/pendaftaran dan pelatihan/pembekalan mahasiswa). Pembekalan internal dilakukan terpisah dan dilaksanakan masing-masing oleh skema tematik KKN, menyesuaikan bekal bagi peserta KKN sebelum bergabung dengan mitra. Aktivitas bersama antara mahasiswa dan masyarakat UKM di POSKO Jasuda, mulai dari pelatihan pengenalan model BMC, proses shaping unit UKM yang sejalan dengan program SIM Advancing dan Coaching Training serta pendampingan selama 1 bulan. Peserta KKN dibagi dalam 10 kelompok untuk mendampingi tenant dan 1 kelompok untuk POSKO Jasuda. Hasil pengabdian KKN-PPM ini menunjukkan impact yang luar biasa terhadap kapasitas maupun keberlangsungan tenant yang semuanya berskala usaha mikro. Kata Kunci: teknologi ICT, BMC, KKN-PPM Dikti